2012
DOI: 10.1177/1479164112448876
|View full text |Cite
|
Sign up to set email alerts
|

Statins and beyond: Concurrent strategies for prevention of cardiovascular disease in patients with type 2 diabetes

Abstract: Diabetes is a significant risk factor for the development of cardiovascular disease (CVD), particularly in the presence of high blood pressure, poor glycaemic control and high total cholesterol. While efforts to control blood pressure or blood glucose beyond levels considered ‘normal’ in patients with diabetes have not produced the expected reduction in CVD, treatment with statins to reduce levels of low-density lipoprotein cholesterol (LDL-C) has been much more successful. However, many patients with diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, cFLC remained independently associated with CVD risk after adjustment for insulin, statins, or ACE inhibitors. Although these treatments have been successful in reducing the risk of CVD in diabetes, the residual risk remained significant and may result from elevated triglyceride levels and chronic inflammation, which have been proposed as additional therapeutic targets (10,11). In this study, a simple risk model including cFLC, SBP, and triglycerides identified the majority of patents suffering CVD events and could therefore be useful in identifying high-risk patients that may benefit from such novel treatments.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, cFLC remained independently associated with CVD risk after adjustment for insulin, statins, or ACE inhibitors. Although these treatments have been successful in reducing the risk of CVD in diabetes, the residual risk remained significant and may result from elevated triglyceride levels and chronic inflammation, which have been proposed as additional therapeutic targets (10,11). In this study, a simple risk model including cFLC, SBP, and triglycerides identified the majority of patents suffering CVD events and could therefore be useful in identifying high-risk patients that may benefit from such novel treatments.…”
Section: Discussionmentioning
confidence: 96%
“…Instead, several authors recommended that correction of hyperglycemia should be combined with statin and lifestyle changes ( 151 , 152 ). Around 2012 several reports proposed that therapy with ω 3-fatty acids may treat HTG and may reduce residual risk in T2DM patients and patients with MetS ( 152 , 153 ). By using lifestyle changes, anti-glycemic agents, and lipid-regulating therapies in patients with T2DM, endothelial function improved as well ( 125 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…High blood pressure, hyperglycemia and dislypidemia are held responsible for the increased risk for cardiovascular disease in MetS and T2DM patients, including microvascular complications (including retinopathy, nephropathy and neuropathy) and atherosclerosis at the macrovascular level [ 1 4 ]. Both high fasting glucose levels and impaired glucose tolerance are associated with increased cardiovascular events [ 5 ], while impaired glucose tolerance predicts cardiovascular death [ 6 ].…”
Section: Introductionmentioning
confidence: 99%